Characterization of the oral microbiome and gut microbiome of dental caries and extrinsic black stain in preschool children - Zheng, Luoyuan; Cao, Tingting; Xiong, Puling; Ma, Yulian; Wei, Limin; Wang, Jianfeng (Frontiers in Microbiology, 2023)
Lower rates of dental caries have been observed in children with the presence of dental extrinsic black stain (EBS). This study sought to investigate the epidemiologic characterization of EBS and explore the possible role the oral and gut microbiome played in the process of EBS formation and caries-preventive mechanism. In an epidemiologic survey, 2675 children aged 3–6 years were included. 38 form 2675were recruited in 16S rRNA sequencing. Supragingival plaque and fecal samples were collected from these 38 children; then, the plaque samples were thereafter divided into the following four groups: BCP (EBS+, caries+), BP (EBS+, caries−), CP (EBS−, caries+), and P (EBS−, caries−). Similarly, the fecal samples were also divided as follows: BCF (EBS+, caries+), BF (EBS+, caries−), CF (EBS−, caries+), and F (EBS−, caries−). EBS was observed in 12.10% of this population. Children with EBS had a significantly lower prevalence of dental caries and mean decayed-mising-filled(dmft) value (p < 0.01). During dental plaque analysis, P had the most complex microbiome. BCP exhibited greater OTU richness but a reduced evenness compared to BP, and CP similarly showed greater OTU richness than BP. At the genus level, higher levels of relative abundance of Actinomyces, Cardiobacterium were observed in BCP. And those of Lautropia and Pesudopropionibacteriumin were observed in BP compared to in P and CP, respectively (p < 0.05). In addition, Veillonella was significantly more common in P and CP than in BP, while Porphyromonas and Fusobacterium were more common in CP (p < 0.05). During gut microbiome analysis, CF exhibited greater OTU diversity than BF. BCF microbiota exhibited the most complex relationships across all fecal groups. Gut microbiome groups may be distinguished by various unique microbiome biomarkers, such as Escherichia and Shigella in BCF, Agathobacter and Ruminococcus in CF, Lactobacillus in BF, and Roseburia in F. The results of this study suggest that EBS is a possible protective factor against early childhood caries. Dental plaque and gut microbiome are possibly relevant to the process of EBS in primary dentition.